Comparison of Peripheral Blood Regulatory T Cells and Functional Subsets Between Ocular and Generalized Myasthenia Gravis - Rao, Jie; Li, Siyu; Wang, Xinyu; Cheng, Qi; Ji, Yu; Fu, Wenwen; Huang, Hui; Shi, Ling; Wu, Xiaorong (Frontiers in Medicine, 2022)
Purpose This study aims to discuss the function mechanism of regulatory T cells and its subsets in the pathogenic process of myasthenia gravis by contracting the activation levels of those cells in peripheral blood among healthy people, patients with ocular myasthenia gravis (oMG) and patients with generalized myasthenia gravis (gMG). Method Healthy people, newly diagnosed oMG patients, and gMG patients were enrolled in this study. The percentage of the CD3+CD4+CD25+ Treg cells, CD3+CD4+CD25+Foxp3+ Treg cells, CD3+CD4+CD25+Foxp3hi CD45RA–aTreg cells, CD3+CD4+CD25+Foxp3loCD45RA–n-sTreg cells, and CD3+CD4+CD25+ Foxp3loCD45RA+rTreg cells in the peripheral blood were examined by flow cytometry. And then analyzed the differences of Treg cells and its subsets among the study members. Results The percentage of the CD4+CD25+Treg cells in the peripheral blood of oMG patients and gMG patients were both lower than that of healthy people (p < 0.05), the percentage of patients with oMG had no distinct difference with that of patients with gMG (p = 0.475), however. Also, the percentage of CD3+CD4+CD25+Foxp3+Treg cells in the oMG and gMG patients’ group were both lower than that of healthy group. And the percentage of CD25+Foxp3+Treg cells in the peripheral blood of patients with oMG and healthy people were both higher than that of patients with gMG (p < 0.05). The percentage of rTreg in the CD3+CD4+CD25+Treg of the peripheral blood for both gMG and oMG patients’ group were lower than healthy group (p < 0.05), but there was no statistical significance between the oMG and gMG patients’ group (p = 0.232). The percentage of the aTreg cells in the CD3+CD4+CD25+Treg cells of the peripheral blood for the oMG patients was higher than that of gMG patients (p < 0.05), but both of them were lower than healthy group (p < 0.05). The percentage of n-sTreg cells in the peripheral blood descended among the gMG patients’ group, oMG patients’ group, and healthy group (p < 0.05). Conclusion The changes in the number and function of Treg cells and its subsets can cause the impairment of negative immune regulation, which may mediate the triggering of oMG and its progression to gMG.